Growth of ZIF‐8 MOF Films with Tunable Porosity by using Poly (1‐vinylimidazole) Brushes as 3D Primers. Issue 54 (2nd September 2020) - Allegretto, Juan A.; Iborra, Agustín; Giussi, Juan M.; von Bilderling, Catalina; Ceolín, Marcelo; Moya, Sergio; Azzaroni, Omar; Rafti, Matias
Abstract: This work reports on a novel and versatile approach to control the structure of metal–organic framework (MOFs) films by using polymeric brushes as 3D primers, suitable for triggering heterogeneous MOF nucleation. As a proof‐of‐concept, this work explores the use of poly(1‐vinylimidazole) brushes primer obtained via surface‐initiated atom transfer radical polymerization (SI‐ATRP) for the synthesis of Zn‐based ZIF‐8 MOF films. By modifying the grafting density of the brushes, smooth porous films were obtained featuring inherently hydrophobic microporosity arising from ZIF‐8 structure, and an additional constructional interparticle mesoporosity, which can be employed for differential adsorption of targeted adsorbates. It was found that the grafting density modulates the constructional porosity of the films obtained; higher grafting densities result in more compact structures, while lower grafting density generates increasingly inhomogeneous films with a higher proportion of interparticle constructional porosity. Abstract : Poly(1‐vinylimidazole) brushes served as heterogeneous nucleation points for ZIF‐8 MOF growth. By modifying the brush grafting density, the films featured inherently hydrophobic microporosity arising from ZIF‐8 structure, and an additional constructional interparticle mesoporosity, which can be employed for differential adsorption of targeted adsorbates.